2010
DOI: 10.1002/art.27523
|View full text |Cite|
|
Sign up to set email alerts
|

Intervertebral disc degeneration: New insights based on “skipped” level disc pathology

Abstract: Objective. Typically, age and abnormal physical loading ("wear and tear") have been associated with the development of intervertebral disc degeneration. In the past decade, various additional etiologic factors for disc degeneration have been sporadically reported in the literature; however, many investigators continue to place tremendous emphasis on the effects of age and biomechanics associated with disc degeneration. The aim of this study was to provide additional insight into the notion that age and biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 68 publications
1
56
1
Order By: Relevance
“…These dissimilarities on the other hand are due to hormonal differences and the onset of menstruation-related pain in women [36]. Nevertheless, disc degeneration is multifaceted, traditionally attributed to age, mechanical loading, gender, trauma, obesity and other factors impairing disc nutrition [37][38][39][40][41].…”
Section: Bdimentioning
confidence: 99%
“…These dissimilarities on the other hand are due to hormonal differences and the onset of menstruation-related pain in women [36]. Nevertheless, disc degeneration is multifaceted, traditionally attributed to age, mechanical loading, gender, trauma, obesity and other factors impairing disc nutrition [37][38][39][40][41].…”
Section: Bdimentioning
confidence: 99%
“…Recently, in the Hong Kong Degenerative Disc Disease Cohort study, which is a population-based study of Southern Chinese patients primarily assessing the phenotype of disc degeneration, Cheung et al [3] in their analysis of 1989 subjects, found a prevalence of 8.1 % and 20 % for SLDD in the overall population and among individuals with multilevel disc degeneration, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The concept of adjacent-level disc degeneration is best noted in spinal fusion cases in which adjacent-level disc changes manifest or are accelerated proximal to an immobile fused segment and taper off as segments become more distal [9-11]. Although single-disc pathology is common, the phenomenon of SLDD is truly unique and is not completely understood [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique occurrence of noncontiguous or skipped levels of disc degeneration (SLDD) of the lumbar spine, with healthy/normal discs between degenerated discs on magnetic resonance imaging (MRI), has been previously reported. 31 Recently, in the Hong Kong Degenerative Disc Disease Cohort study, which is a population-based study of Southern Chinese patients primarily assessing the phenotype of disc degeneration, Cheung et al , 32 in their analysis of 1989 subjects, found a prevalence of 8.1% and 20% for SLDD in the overall population and among individuals with multilevel disc degeneration, respectively.…”
mentioning
confidence: 98%